Social Criticism: Charlotte’s Web Analysis - Ardayati, Ardayati; Ramasari, Maria (JURNAL PERSPEKTIF PENDIDIKAN, 2025)
Aim of this analysis was to describe social criticism in Charlotte’s Web. Descriptive qualitative method was applied in analyzing. Novel became main focus to be analyzed. Unfair friendship like a toxic friendship and bad relationship between characters in the novel are found as the social critics. Besides, It was also analyzed that a complicated friendship was happen and left a conflict like different perspective on the way someone though about life. There was no willingness to listen to and discuss with partners. Trust became one point that was analyzed. Trust to others was so essential. When one believed in others so all things run well becuse there was a respectable eachother. In addition, social criticsm was also seen in this novel by analyzing that friend was widely loved and care about but it is not as beautiful as thought by writer. Social problems and classification like what was called by bad circle that gave a very strong influence to the way one interact with others.